2022
DOI: 10.3390/app12031069
|View full text |Cite
|
Sign up to set email alerts
|

NOx–Smoke Trade-off Characteristics in a Palm Oil-Fueled CRDI Diesel Engine under Various Injection Pressures and EGR Rates

Abstract: Palm oil is one of the most common and productive vegetable oils, so it is often used as an excellent feedstock for biodiesel production. However, due to the high viscosity and other issues of palm oil, it cannot be directly used as an alternative fuel for diesel engines unless some treatment is carried out. In this study, the effects of palm oil-diesel blend fuel on the nitrogen oxides (NOx)–smoke trade-off characteristics were investigated in a common rail direct injection (CRDI) diesel engine under various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although some fuel blends increase carbon monoxide quantity, other reaction products, such as nitrous oxides and hydrocarbons, were reduced, improving CRDI engine combustion characteristics. Similarly, dimethyl ether or biodiesel and hydrogen combinations improved performance, as mentioned in [43,44]. The hydrogen addition reduced all three harmful exhaust compounds while decreasing the brake thermal factor, improving engine efficiency.…”
Section: Improving Renewability Of Direct Injection Fuel Systemsmentioning
confidence: 69%
See 1 more Smart Citation
“…Although some fuel blends increase carbon monoxide quantity, other reaction products, such as nitrous oxides and hydrocarbons, were reduced, improving CRDI engine combustion characteristics. Similarly, dimethyl ether or biodiesel and hydrogen combinations improved performance, as mentioned in [43,44]. The hydrogen addition reduced all three harmful exhaust compounds while decreasing the brake thermal factor, improving engine efficiency.…”
Section: Improving Renewability Of Direct Injection Fuel Systemsmentioning
confidence: 69%
“…Adding crude palm oil resulted in a trade-off in emission and performance characteristics. A change in fuel properties also results in a change in CRDI engine performance, having various percentage biofuel mixtures being tested and resulting in a different performance for each study [44,45]. For example, adding the decarbonizing additive to the PB20 fuel mixture resulted in lower efficiency, as shown in Figure 9.…”
Section: Improving Renewability Of Direct Injection Fuel Systemsmentioning
confidence: 99%
“…It was found that inlet air temperature had a strong influence on low temperature reaction and HCCI combustion timing, while a higher premixed ratio had more influence on reducing NOx emissions. Wu et al [23] investigated the influence of palm oil diesel blends on Nox-smoke trade off characteristics in a CRDI diesel engine at different engine pressures and exhaust recirculation conditions. It was understood that, at high injection pressure, the smoke formation reduced but NOx emissions increased.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel engines show poor cold start performance at low temperatures, for instance, high emissions, high fuel consumption and long cranking time [1]. Various methods were investigated to improve the engine performance, including pilot injection [2,3], fuel optimization [4][5][6][7][8][9], thermal barrier coating [10] and intake air preheating [11]. However, diesel engines still face great challenges.…”
Section: Introductionmentioning
confidence: 99%